2017
DOI: 10.1371/journal.pone.0174547
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of monomeric periostin as a biomarker for idiopathic pulmonary fibrosis

Abstract: The natural course of idiopathic pulmonary fibrosis (IPF) is variable. Predicting disease progression and survival in IPF is important for treatment. We previously demonstrated that serum periostin has the potential to be a prognostic biomarker for IPF. Our aim was to use monomeric periostin in a multicenter study to evaluate its efficacy in diagnosing IPF and predicting its progression. To do so, we developed a new periostin kit to detect only monomeric periostin. The subjects consisted of 60 IPF patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 38 publications
5
91
1
Order By: Relevance
“…24 On the other hand, high amounts of POSTN could interact with TNFα or IL-1α in fibroblasts to stimulate NF-κB that could result in lung fibrosis. 25 It is well known that high serum POSTN can be a predictive marker for effective anti-IL-13 antibody treatment in asthmatic patients 26 and a prognostic marker for increased risk of asthma exacerbations and progressive decline in lung function. 6 However, whether increased POSTN expression has protective or deleterious effects in asthma, is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 On the other hand, high amounts of POSTN could interact with TNFα or IL-1α in fibroblasts to stimulate NF-κB that could result in lung fibrosis. 25 It is well known that high serum POSTN can be a predictive marker for effective anti-IL-13 antibody treatment in asthmatic patients 26 and a prognostic marker for increased risk of asthma exacerbations and progressive decline in lung function. 6 However, whether increased POSTN expression has protective or deleterious effects in asthma, is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that POSTN deficient mice challenged with inhaled aeroallergen showed an exaggerated serum IgE and bronchial hyperresponsiveness that might be due to the POSTN effect on TGF-β-induced T regulatory cell differentiation. 25 Moreover, POSTN deficiency was shown to enhance polyps like lesion formation and mast cell infiltration. 27 Technical challenges that hinder the use of POSTN include post-translational modifications as well as the existence of multiple differentially spliced isoforms in various proportions in diverse tissues and disease states.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, ATII cell dysfunction is a common feature of fibrotic lungs [ 23 ]. Periostin expression is elevated in lung tissue and blood of patients with IPF [ 24 , 25 ], however it remains unclear if alveolar epithelial cells contribute. Although ATII cells produce various profibrotic cytokines such as TGF-beta [ 26 , 27 ], it is unknown whether they produce periostin at the normal and diseased conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Serum periostin is elevated both the acute phase and the chronic stable phase in IPF patients [21,22].…”
Section: Biomarkermentioning
confidence: 99%